ASESMEN AKHIR KEMAMPUAN LITERASI BACA TULIS SISWA FASE A UPTD SDN SOBO : IMPLEMENTASI PROGRAM KDS 2023 - Emiliana Wae; Yosefina Uge Lawe; Dek Ngurah Laba Laksana; Maria Desidaria Noge; Noni Stephana Ariany Lodo; Bergita Raga; Kristina Kedhi (STKIP Subang, 2024)
The aim of this research is to carry out a final assessment of reading and writing literacy skills which consist of aspects of recognizing letters, writing letters, reading syllables, reading words, reading comprehension and focus on writing sentences. The focus of the study is the final analysis of reading and writing literacy with the target class being grade students. 1, totaling 13 people and class 2 students, totaling 20 students. This research method uses descriptive qualitative with the instruments used are observation, interviews, documentation. The results of the final assessment of the reading and writing literacy skills of UPTD SDN Sobo students for class 1 students in the aspect of getting to know letters increased by 69%, letter writing aspects increased by 23%, syllable reading aspects increased by 30%, word reading aspects increased by 15%, comprehension aspects increased by 7.6%, sentence writing aspects increased by 23%.Data analysis The final reading and writing literacy skills of class 2 students in the aspect of recognizing letters increased by 13.6%, the aspect of writing letters increased by 18.1%, the aspect of reading syllables increased by 4.5%, the aspect of reading words increased by 40.9%, reading understanding increased by 36.3%, writing sentences increased by 27.2%. Based on the final assessment data on the reading and writing literacy skills of UPTD SDN Sobo students, it can be concluded that there was an increase in students' literacy skills after mentoring in LPTK Lecturer Partnership activities with Teachers at School year 2023.